Goal‐Oriented Requirements Engineering for Research‐Intensive Complex Systems: A Case Study. Issue 4 (16th August 2016) - Woldeamlak, Selamawit; Diabat, Ali; Svetinovic, Davor
ABSTRACT: Complex systems in research and development exhibit important characteristics that might present significant systems engineering challenges due to lack of clear customers, system goals, previous development experience, etc. Such systems are characterized through the existence of multiple proposed preliminary architectures, no implemented prototypes, and no agreed upon standards and protocols. We refer to these systems as Research‐Intensive Complex Systems (RICS). RICS requirements are not well‐defined, and RICS are exposed to a wide variety of risks and uncertainties. The main source of the RICS domain knowledge, requirements, and goals are research publications and reports. There is often a lack of clear goals, and many goals are ambiguous or conflicting. This paper evaluates the effectiveness of the Knowledge Acquisition in autOmated Specification (KAOS) method applied to smart metering system, as an example of a sustainability‐related RICS. The evaluation is performed using a set of qualitative criteria with respect to KAOS's ability to elicit and specify goals for RICS in comparison to the implemented goal models.